Mean-Variance Hedging under Additional Market Information - Frank Thierbach (University of Bonn, Bonn Graduate School of Economics (BGSE), 2002)
In this paper we analyse the mean-variance hedging approach in an incomplete market under the assumption of additional market information, which is represented by a given, finite set of observed prices of non-attainable contingent claims. Due to no-arbitrage arguments, our set of investment opportunities increases and the set of possible equivalent martingale measures shrinks. Therefore, we obtain a modified mean-variance hedging problem, which takes into account the observed additional market information. Solving this by means of the techniques developed by Gourieroux, Laurent and Pham (1998), we obtain an explicit description of the optimal hedging strategy and an admissible, constrained variance-optimal signed martingale measure, that generates both the approximation price and the observed option prices.
Keywords: G12; G11; 330; option pricing; mean variance hedging; incomplete markets; varianceoptimal martingale measure; Hedging; Optionspreistheorie; Portfolio-Management; Theorie; mean variance approach